Cryptococcus laurentii fungemia in a low birth weight preterm neonate: India - Minakshi Gupta; Asit K. Mishra; Santosh K. Singh (Elsevier, 2018)
In the last few years, Cryptococcus laurentii infections have increased, particularly in immunocompromised patients. Here we report the first case of C. laurentii fungemia in low birth weight preterm infant from India. A preterm neonate was admitted for feeding intolerance and respiratory distress. Blood culture ascertained the causative organism as C. laurentii. The isolated strain was found susceptible to amphotericin B and the patient recovered following the administration of amphotericin B (5 mg/kg body weight) for 8 days. Keywords: Cryptococcus laurentii, Neonate, Fungemia, Amphotericin B